ANALISIS STRATEGI PEMASARAN DENGAN MENGGUNAKAN METODE SWOT DAN ANALYTICAL HIERARCHY PROCESS (AHP) UNTUK MENINGKATKAN VOLUME PENJUALAN - murni novita sijabat (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2019)
Father's Bakery Bakery is a Home Industry that is engaged in the processing of food bread and various types of cakes. The problem that occurred was Father's Bakery was experiencing a decline in terms of product image and income. The purpose of this research is to find out the factors that influence the marketing strategy and give the right marketing strategy proposals for Papa Bakery Bakery. Determination of the position of the IE matrix strategy is based on the results of the total value of the IFE matrix which biberi weights on the X axis and the total value of the EFE matrix on the Y axis. (Growth). Based on the results of the swot matrix there are 12 strategies. The final stage in this study is the selection of the chosen strategy to be implemented in the Papa Bakery Bakery by using the analytical hierarchy process (AHP). The results obtained then the chosen strategy is to implement an online sales system to expand the market.